The emotions of elderly people from the rural population - Dziechciaż, Małgorzata; Płaszewska-Żywko, Lucyna; Guty, Edyta (Polish Journal of Public Health, 2010)
Introduction. The aim of the study was to estimate the emotions of elderly people in the rural population.Material and methods. The study was carried out among 102 people (56 females and 46 males), 60-86 years old (average 73.18) in the Podkarpacie Province. The investigated group was intellectually active. The research was based on a self-made questionnaire, Hodkinson’s Abbreviated Mental Test Score, Yesavage’s Geriatric Depression Scale, Katz (ADL) Scale, Lawton Scale (IADL).Results. The majority of the investigated group (71.6%) were the people in the correct emotional state. It has been found out that the emotional condition deteriorates when people get older (p